Breastfeeding practices in the United Kingdom: Is the neighbourhood context important?. Issue 4 (17th May 2018) - Peregrino, Andressa B.; Watt, Richard G.; Heilmann, Anja; Jivraj, Stephen
Abstract: Breastfeeding is an important public health issue worldwide. Breastfeeding rates in the United Kingdom, particularly for exclusive breastfeeding, are low compared with other OECD countries, despite its wide‐ranging health benefits for both mother and child. There is evidence that deprivation in the structural and social organisation of neighbourhoods is associated with adverse child outcomes. This study aimed to explore whether breastfeeding initiation, exclusive breastfeeding for at least 3 months, and any type of breastfeeding for at least 6 months were associated with neighbourhood context measured by neighbourhood deprivation and maternal neighbourhood perceptions in a nationally representative U.K. sample. A cross‐sectional analysis was conducted using data from the Millennium Cohort Study. Logistic regression was carried out on a sample of 17, 308 respondents, adjusting for individual‐ and familial‐level socio‐demographic characteristics. Neighbourhood deprivation was independently and inversely associated with breastfeeding initiation. Compared with the least deprived areas, the likelihood of initiating breastfeeding was 40% lower in the most deprived neighbourhoods (OR: 0.60, 95% CI [0.50, 0.72]). The relationship between both exclusive and any type of breastfeeding at 3 and 6 months respectively with neighbourhood deprivation after adjustment for potential confounders was not entirely linear. Breastfeeding initiation (OR: 0.78, 95% CI [0.71, 0.85]), exclusivity for 3 months (OR: 0.84, 95% CI [0.75, 0.95]), and any breastfeeding for 6 months (OR: 0.82, 95% CI [0.73, 0.93]) were each reduced by about 20% among mothers who perceived their neighbourhoods lacking safe play areas for children. Policies to improve breastfeeding rates should consider area‐based approaches and the broader determinants of social inequalities.